Short-term fairness in slotted WDM rings - Bianco, Andrea (2015)
Single-hop WDM ring networks are promising architectures for future broadband access and metro networks. However, ring networks exhibit significant fairness issues, which must be handled by a fairness enforcing protocol. Fairness is usually ensured over a time window of several network propagation delays. Thus, data flows might experience large access delays which might be not compatible to support time-sensitive applications. We solve this issue proposing the Multi-Fasnet protocol, which is able to enforce fairness in a relative short time scale, in the order of few propagation delays, without trading off the aggregated throughput network performance. We discuss Multi-Fasnet limitations and propose several novel strategies that achieve high and fair network throughput as well as low, bounded and fair access delays.